2018
DOI: 10.1111/1759-7714.12898
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigation of the efficacy and toxicity of apatinib (YN968D1) in stage III/IV non‐small cell lung cancer after second‐line chemotherapy treatment: A retrospective study

Abstract: BackgroundThis study was designed to assess the clinical efficacy and toxicity of apatinib (YN968D1) as third or subsequent‐line treatment for stage III/IV non‐small cell lung cancer (NSCLC).MethodsA total of 100 patients with advanced NSCLC who were treated with apatinib at a daily dose of 250/425/500 mg at Shandong Cancer Hospital from January 2016 to June 2018 were enrolled in our study. The objective response, disease control, and median progression‐free survival rates were reviewed and evaluated. Univaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 61 publications
(113 reference statements)
0
15
0
Order By: Relevance
“…12,13 Recent studies have also shown its efficacy in patients with NSCLC. [14][15][16][17] We previously reported that low-dose apatinib (250 mg/day) monotherapy resulted in similar PFS to higher-dose apatinib (500-750 mg/day) in patients with NSCLC, 16,17 and was associated with fewer adverse effects in these studies. In a recent case report, apatinib (425 mg/day) combined with pneumonectomy and/or radiotherapy was used in two patients with relapsed SCLC, 18,19 and two other studies also reported on the use of apatinib as maintenance therapy in patients with stable SCLC after induction chemotherapy.…”
Section: Introductionmentioning
confidence: 78%
“…12,13 Recent studies have also shown its efficacy in patients with NSCLC. [14][15][16][17] We previously reported that low-dose apatinib (250 mg/day) monotherapy resulted in similar PFS to higher-dose apatinib (500-750 mg/day) in patients with NSCLC, 16,17 and was associated with fewer adverse effects in these studies. In a recent case report, apatinib (425 mg/day) combined with pneumonectomy and/or radiotherapy was used in two patients with relapsed SCLC, 18,19 and two other studies also reported on the use of apatinib as maintenance therapy in patients with stable SCLC after induction chemotherapy.…”
Section: Introductionmentioning
confidence: 78%
“…Our study demonstrated that low dose apatinib combined with pemetrexed could provide beneficial clinical outcomes and a favorable safety profile in advanced NSCLC patients. In this study, apatinib combined with pemetrexed produced a median PFS of 7.0 months, while the median PFS of apatinib monotherapy in patients with advanced nonsquamous NSCLC was 2.93 months in a phase II trial (14), indicating that apatinib combined with pemetrexed could provide effective clinical outcomes after failure of previous chemotherapy. Furthermore, apatinib monotherapy (250 to 750 mg qd) produced a median PFS and median OS of 3 (95% CI: 2.6-3.4) and 7.4 (95% CI: 1.3-13.5) months, respectively, in advanced non-squamous NSCLC after multi-line treatments (29).…”
Section: Discussionmentioning
confidence: 63%
“…Apatinib has been approved for the third-line or beyond treatment of advanced or metastatic gastric cancer recurrent from chemotherapy in China. At the same time, apatinib has shown potential anti-tumor activity in the treatment of several solid tumors, whatever in monotherapy or combination with other antitumor agents (10)(11)(12)(13)(14)(15). Furthermore, apatinib has been demonstrated to benefit patients of pretreated advanced NSCLC with a median PFS of 4.0 months in a retrospective study (12).…”
Section: Introductionmentioning
confidence: 99%
“… 24 These efficacy differences highlighted the gap between randomized controlled clinical trials and actual clinical practice. 25 Patients with an ECOG score of 2 were included in our study as well. To our knowledge, the influence of ECOG score on prognosis has been confirmed in many studies, which indicate that higher PS scores have worse prognoses.…”
Section: Discussionmentioning
confidence: 99%